FOUR MAJOR HEALTH PROBLEMS IN PRODUCTIVE-AGE WOMEN (HYPERTENSION, HYPERURICEMIA, HYPERGLYCEMIA, AND HYPERCHOLESTEROLEMIA): A DESCRIPTIVE STUDY IN BULO VILLAGE, KAB. ENREKANG - Dewi Hestiani K; Fardi (Media Inovasi Pendidikan dan Publikasi, 2024)
This study was conducted in Bulo Village, Bungin Sub-district, Enrekang Regency, in January 2024, to evaluate the prevalence of hypertension, hyperuricemia, hyperglycemia, hypoglycemia, and hypercholesterolemia among women of reproductive age. A total of 50 women aged 15-49 years participated in this study. The age distribution of the respondents showed that the majority were in the 40-44 age range (26%), followed by the 35-39 age range (20%) and the 45-49 age range (20%). The results showed that 10 women (20%) had hypertension (blood pressure ≥ 140/90 mmHg), 18 women (36%) had hyperuricemia (serum uric acid levels ≥ 6 mg/dL), and 20 women (40%) had hypercholesterolemia (total cholesterol levels ≥ 200 mg/dL). No cases of hyperglycemia (blood glucose levels ≥ 200 mg/dL) or hypoglycemia (blood glucose levels < 70 mg/dL) were found in the sample studied. Hypercholesterolemia was the most common condition, followed by hyperuricemia and hypertension. These findings indicate the need for more intensive health interventions in the community. Education on healthy eating habits, physical activity, and regular health check-ups are essential to manage and prevent further complications from these conditions. This study provides valuable insights into the health status of women of reproductive age in Bulo Village and underscores the importance of appropriate preventive measures.